DETERMINAN KINERJA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) STUDI KASUS : FORUM UMKM ONLINE DI KABUPATEN KEBUMEN - Fathurrahman, Ayif; Setiana, Nana Dwi (Forum Bisnis Kewirausahaan, 2024)
This study aims to determine the factors that affect the perfomance of micro, small and medium enterprises (SMEs) of the online SMEs forum in Kebumen Regency. This research involving 2 kind variabels. Independent variabels are capital, technology, and human resource. The dependent variabel is perfomance of SMEs. Data were analyzed using multiple linear regression which is supposed by primary data. Respondents in the study amounted to 41 respondents drawn from resesarch survey data and using saturated samples. Based on the analysis shows that : (1) The capital is possitive and significant to the perfomance of SMEs of the online SMEs forum in Kebumen Regency; (2) Technologi is possitive and significant to the perfomance of SMEs of the online SMEs forum in Kebumen Regency; (3) Human Resources is possitive and significant to the perfomance of SMEs of the online SMEs forum in Kebumen Regency.